Cherry stem infusions: antioxidant potential and phenolic profile by UHPLC-ESI-QTOF-MS. Issue 4 (3rd April 2020) - Peixoto, Juliana; Álvarez-Rivera, Gerardo; Alves, Rita C.; Costa, Anabela S. G.; Andrade, Nelson; Moreira, Andreia; Cifuentes, Alejandro; Martel, Fátima; Oliveira, M. Beatriz P. P.; Ibáñez, Elena
Abstract : This study highlights not only the antioxidant potential of cherry stem infusion but also the need to globally harmonize the control and regulation of herbal products. Abstract : The antioxidant potential and phenolic profile of infusions prepared with cherry stems from different commercial brands were studied. The phenolic profile of each infusion was characterized by UHPLC-ESI-QTOF-MS and 44 phenolic compounds belonging to eight distinct classes (hydroxybenzoic acids, hydroxycinnamic acids, phenylpropanoic acids, flavan-3-ols, flavonols, flavanones, flavones and isoflavones) were tentatively identified. For the first time, salicylic acid was identified in cherry stem infusions. In cell-based assays, all the infusions tended to inhibit lipid peroxidation and presented no cytotoxicity. Significant differences ( p < 0.05) were found between a sample sold in bulk (lower antioxidant activity by DPPH˙ inhibition, ferric reducing antioxidant power, and oxygen radical absorbance capacity assays; lower amounts of total phenolics and flavonoids and a different quantitative phenolic profile) and samples sold in packages. These, in turn, were very similar to each other and revealed a high antioxidant potential and a very rich phenolic profile. These results reflect not only the antioxidant potential of cherry stem infusions but also the need to globally harmonize the control and regulation of herbal products in order to ensure in the market products with high quality, safety and efficacy.